Probiotic Effects Of Lactobacillus Strains On Cecal Microbiota And Fermentation, Intestinal Development And Response To Human Contact In Broiler Chickens - Meimandipour, Amir (2010)

(untitled)
The aim of this study was to evaluate the probiotic effects of Lactobacillus agilis JCM 1048 and Lactobacillus salivarius subsp. salicinius JCM 1230 under in vitro and in vivo conditions. In the first in vitro experiment, batch bioreactor system was used to assess the effects of two Lactobacillus strains on selected bacterial groups, short chain fatty acids (SCFAs) and lactate concentrations. In this experiment, 24 h incubation was done in a simulated chicken cecum, at two pH values. The addition of L. agilis JCM 1048 and L. salivarius subsp. salicinius JCM 1230 significantly (P<0.05) increased number of total anaerobes (19%), lactobacilli (18%) and bifidobacteria (27%) at pH 5.8 while decreased those of aerobes (pH=5.8, 13% & pH=6.7, 9%) and streptococci (22% in both pH values) in (Cc+L) treatment group after 24 h incubation as compared to (Cc) group (Table 3.1). The supplementation with lactobacilli was found to increase the production of lactate, propionate and butyrate (pH=5.8, 256% & pH=6.7, 246%), while suppressed the concentration of acetate (Table 3.3).